PSYCHOSOCIAL STRESS: SOME CLINICAL AND EXPERIMENTAL ASPECTS - Molina-Jiménez, Tania; Gutiérrez-García, Ana G.; Hernández-Domínguez, Lizette; M. Contreras, Carlos (Anales de Psicología / Annals of Psychology, 2008)
The present revision approaches the definition of the concept of stress generated by different social factors. Psychosocial stress induces diverse pathologies in human being, contributing to health perturbation. The study of the effects of psychosocial stress in the human is limited since methodological and ethical considerations; however, the observation of the strategies to cope with stress in animal models, as well as its neurobiological correlates is a useful tool for the neurobiological study of psychosocial stress. For example, in the social defeat the display some signs suggesting an increased anxiety and despair, both processes involve the participation of the amygdala, and from some clinical studies in human it has additionally been suggested the involvement of the prefrontal cortex portion, in the decision-making process and the selection of the socially appropriated response.